Estimation of hourly, daily and monthly global solar radiation on inclined surfaces: models re-visited - Maleki, Seyed Abbas Mousavi; Hizam, Hashim; Chandima Gomes, Gorakanage Arosha (MDPI, 2017)
Global solar radiation is generally measured on a horizontal surface, whereas the maximum amount of incident solar radiation is measured on an inclined surface. Over the last decade, a number of models were proposed for predicting solar radiation on inclined surfaces. These models have various scopes; applicability to specific surfaces, the requirement for special measuring equipment, or limitations in scope. To find the most suitable model for a given location the hourly outputs predicted by available models are compared with the field measurements of the given location. The main objective of this study is to review on the estimation of the most accurate model or models for estimating solar radiation components for a selected location, by testing various models available in the literature. To increase the amount of incident solar radiation on photovoltaic (PV) panels, the PV panels are mounted on tilted surfaces. This article also provides an up-to-date status of different optimum tilt angles that have been determined in various countries.